2013
DOI: 10.1093/glycob/cwt021
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated Neu5Ac-Tn and Neu5Gc-Tn antigens bind to C-type lectin CLEC10A (CD301, MGL)

Abstract: In human tumors, glycoproteins often exhibit abnormal glycosylation patterns, e.g. certain Lewis structures, TF antigen, Tn antigen and/or their sialylated forms, creating additional binding sites for glycoreceptors. In the present study, we have analyzed the carbohydrate specificity of the C-type lectin CLEC10A using glycan profiling by enzyme-linked immunosorbent assay (ELISA). In addition to the known ligands, we show binding to two tumor-associated antigens, namely Neu5Acα2,6-Tn and Neu5Gcα2,6-Tn, with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 29 publications
5
72
0
Order By: Relevance
“…The similarity of the rupture force and lifetimes of the MUC1(Tn) and MUC1(STn) interaction with MGL (Tables 2 and 3) is consistent with the main conclusions drawn based on previous NMR data, which indicated a similar binding mode for the Tn and the sialylated Tn antigen when interacting with MGL [30]. The NMR data indicated that the N-acetyl group and the H-2, H-3 and H-4 protons of the GalNAc residue made the major contribution to the interaction [30]. However, the NMR data also indicated a slightly lower affinity of the STn antigen for MGL compared to the Tn antigen [30].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The similarity of the rupture force and lifetimes of the MUC1(Tn) and MUC1(STn) interaction with MGL (Tables 2 and 3) is consistent with the main conclusions drawn based on previous NMR data, which indicated a similar binding mode for the Tn and the sialylated Tn antigen when interacting with MGL [30]. The NMR data indicated that the N-acetyl group and the H-2, H-3 and H-4 protons of the GalNAc residue made the major contribution to the interaction [30]. However, the NMR data also indicated a slightly lower affinity of the STn antigen for MGL compared to the Tn antigen [30].…”
Section: Discussionsupporting
confidence: 90%
“…Provided the molecular interaction possesses an inner energy barrier in the energy landscape, the characterization by AFM may yield lower x β values [49]. The similarity of the rupture force and lifetimes of the MUC1(Tn) and MUC1(STn) interaction with MGL (Tables 2 and 3) is consistent with the main conclusions drawn based on previous NMR data, which indicated a similar binding mode for the Tn and the sialylated Tn antigen when interacting with MGL [30]. The NMR data indicated that the N-acetyl group and the H-2, H-3 and H-4 protons of the GalNAc residue made the major contribution to the interaction [30].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations